PENGARUH JAM’ AL-QURAN PADA MASA NABI MUHAMMAD SAW DAN KHULAFAURRASYIDIN DALAM MENINGKATKAN TEOLOGI DALAM KALANGAN MUSLIM AWAM - Devy Wulandari; Nasrullah Bin Sapa (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The authenticity of the Qur'an that is preserved cannot be separated from the process of collecting, writing and unifying. This process is called jam' al-Quran, or the process of codifying the Qur'an. Of course, this process has a very important role so that the authenticity of the Qur'an has been maintained for centuries since it was revealed until now. The mushaf of the Qur'an that we have now turned out to have gone through a long and winding journey over a period of more than 1400 years ago and has an interesting historical background to know. Historically, the journey of Qur'an bookkeeping is indeed not as complex as hadith bookkeeping. However, this does not mean that the process of codification of the Qur'an is not interesting to study. In its journey, the Qur'an in the sense of its capacity as a book or a bound sheet of paper and written in it which is considered by Muslims to be the revelation of Allah—the process of codification is no longer normative, but very historical, because it is related to various kinds of discourses/discourses (social, political, and others) that surround it, so that it is always worthy of questioning and discussion anytime, anywhere, and even by anyone. We already know that the Qur'an was revealed gradually. The Prophet received the Qur'an through the angel Gabriel and then he recited and dictated it to the companions who listened to it. The collection of the Qur'an during the time of the Prophet was grouped into two categories, namely: collection in the chest in the form of memorization and appreciation and collection in records in the form of book writing.